2020
DOI: 10.1002/hed.26067
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of NUT carcinoma in head and neck: Analysis of 362 cases with literature review

Abstract: Background: Nuclear protein in testis (NUT) carcinoma is a poorly differentiated carcinoma defined by the presence of NUT gene rearrangement. In the head and neck, the true prevalence of NUT carcinoma is unknown. Methods:We retrospectively investigated NUT expression with clinicopathologic features in 362 patients of poorly differentiated or undifferentiated carcinomas in the head and neck, and reviewed the literature reports.Results: Four (4/362, 1.1%) cases showed strong nuclear expression for NUTspecific mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…NUT-C is considered a very rare entity, but the true prevalence in the head and neck is indeed unknown. Recently, Lee et al [7] reported that NUT-C accounts for 2.9% and 12.5% of poorly or undifferentiated carcinomas arising in the head and neck and sinonasal tract, respectively. Furthermore, the authors confirmed that the sinonasal tract represents the most common initial presenting site of the head and neck (73.4%), followed by the salivary glands (11%), larynx (7.3%), pharynx (4.6%), and oral cavity (3.7%).…”
Section: Epidemiologymentioning
confidence: 99%
“…NUT-C is considered a very rare entity, but the true prevalence in the head and neck is indeed unknown. Recently, Lee et al [7] reported that NUT-C accounts for 2.9% and 12.5% of poorly or undifferentiated carcinomas arising in the head and neck and sinonasal tract, respectively. Furthermore, the authors confirmed that the sinonasal tract represents the most common initial presenting site of the head and neck (73.4%), followed by the salivary glands (11%), larynx (7.3%), pharynx (4.6%), and oral cavity (3.7%).…”
Section: Epidemiologymentioning
confidence: 99%
“…IHC slides were interpreted by two independent pathologists (YAC and JHH) as previously described. 13 Antibody against anaplastic lymphoma kinase (ALK) (clone 5A4; 1:30, Novocastra, Newcastle upon Tyne, UK) was used and evaluation of ALK IHC expression was done as previously described. 18 PD-L1 expression was evaluated using PD-L1 IHC 22C3 pharmDx assay (Dako, Glostrup, Denmark) as previously described.…”
Section: Immunohistochemical Staining Interpretation and Fluorescence In Situ Hybridization Assaymentioning
confidence: 99%
“…15,16 Approximately 70% of NUT carcinoma cases are associated with BRD4-NUT fusion and in the remaining 30%, NUT has been previously reported to fuse with BRD3 or other unknown genes. 13,17 In this study, we retrospectively analyzed patients with pulmonary NUT carcinoma diagnosed by NUT immunohistochemical staining and discuss the differential diagnosis to provide information for this rare and aggressive entity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations